HEALTHY LIFESTYLE AND ITS PROMOTION AMONG YOUTH - Saidova Madinabonu Abduhakim qizi (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
This paper examines the importance of a healthy lifestyle and the methods used to promote it among young people. As modern lifestyles become increasingly sedentary and technology-driven, issues such as poor nutrition, lack of physical activity, and mental health challenges are becoming more prevalent among youth. The study emphasizes the need for comprehensive health education, public awareness campaigns, and community-based programs that encourage balanced nutrition, regular exercise, and positive mental habits. Through analysis of both global practices and local initiatives, the paper identifies effective strategies for motivating youth to adopt healthier choices and build lifelong wellness habits. The findings suggest that early intervention and culturally relevant approaches play a critical role in sustaining a healthy lifestyle among the younger generation.